Best Answer

Presumably you are talking about the equation 15x=60 In this case, dividing by 15 would be appropriate, giving x=4.

If you were feeling less confident, you could first divide by 3 to give 5x=20 and then by 5 to give x=4 again.

User Avatar

Wiki User

12y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What number would you use to divide both sides of the equation 15x 60?
Write your answer...
Still have questions?
magnify glass
Related questions

How would you get the variable m alone on one side of the equation 15m equals 45?

Divide both sides of the equation by 15

What is greater then 42?

in an equation it would be 7n>42 (divide both sides by 7) = n>6

What is 7n greater then 42?

in an equation it would be 7n>42 (divide both sides by 7) = n>6

What is a 2 step equation that equals 7?

2x - 5 = 7 First, you would have to add 5 to both sides then, you would have to divide 2 by both sides. The answer is 6

3 plus 4b 7-2b?

If you mean 3+4b=7-2b, then you would start out with that equation I just listed. Then, you would add 2b to both sides, taking you to 3+6b=7. Then, you would subtract 3 from both sides, taking you to 6b=4. Lastly, you would divide both sides by 6, taking you to b=4/6, or 2/3. (Two-thirds)Keep in mind that when you divide or subtract a number from both sides, the side in which it was on (ex. 4b=8), loses that number (4) and only affects THAT number. That is, on the side in which it was ON. Then, when you divide, it affects the otherside of the equation in the same way, but this time affecting any and ALL numbers and variables. In this case, the ex. would turn out to be b=2. But if it had originally been 4b=8+b, then it would turn out to be b= 2+(b/4).

4.8 is 15 of what?

The question "4.8 is 15 of what" can be translated into an algebraic equation which would be, 15x = 4.8 To solve this equation, divide both sides by 15 and you get x = 4.8/15 = .32 which is the answer.

How do you solve this two step equation -737-8x?

First you would take -737 to the other side of the equation -8x = 737 Then you would divide both sides by -8 x = 737/ -8 = -92.125

What is 3y-7y3?

It looks like the first half of an equation. If the full equation is "3y-7y^3=0" then you would need to solve for "y". add 7y^3 to both sides divide both sides by y divide both sides by 7 You get 3/7 = y^2 take the square-root of both sides to get y = sqrt(3/7) or approximately 0.654

How do you solve a one multi-step equation with fractions?

multiply both sides by the lcd then you would take the letter as in x and multiply it by the answer you got and subtract the second answer, then divide both sides by the answer that would be like 3x so u would divide it by 3 on both sides. This may sound confussing to u but if it does then im sorry cuz this stuff is bs.

8 less than 7 times a number is the same as 4 more than 3 times the number?

You want to start by writing an equation with a variable (x) as the number you're looking for. The equation would be 7x-8=4+3x. Subtract 3x from both sides, to get 4x-8=4, and then add 8 to both sides to get 4x=12, then divide by 4 to solve for x. x=3

What is the easiest way to solve inequalities?

It is very similar to solving an equation. You can add or subtract the same term from both sides. In addition, you can multiply or divide both sides by the same thing. A couple of things to note, though, if you multiply or divide both sides by a negative number, the inequality must be flipped [greater than (>) becomes less than (

How do you solve 9y-818-4y?

I assume you are solving for y. First you need to form an equation since you don't have an equal sign. The equation would be 9y - 818 - 4y = 0. Next, you have to isolate the unkown number from the known number by adding 818 to both sides of the equation and you would have 9y - 818 - 4y + 818 = 0 + 818, then your equation would read 9y - 4y = 818. Simplify the unknown number by subtracting 4y from 9y which now makes the equation 5y = 818. To find the value of y, divide both sides of the equation by 5. Hence 5y/5 = 818/5. Thus, y = 163.6. To prove the solution, substitute 163.6 for y and solve.